Chronic ulcerative stomatitis: A systematic review of the clinical and microscopic features - Ferrisse, Túlio Morandin [UNESP]; Travassos, Daphine Caxias [UNESP]; Rocha, Audrey Foster Lefort [UNESP]; Massucato, Elaine Maria Sgavioli [UNESP]; Bufalino, Andreia [UNESP] (Medicina Oral, S.L., 2019)
Background: the purpose of this study was to perform a systematic review regarding clinical and histopathological characteristics, immunopathological findings, and treatment for chronic ulcerative stomatitis (CUS). Material and Methods: articles in English, published from January 1962 up to November 2017, assessing clinical and immunological features, treatment, and follow-up of patientes with CUS, were retrieved from three databases (PubMed, Cochrane Library and SCOPUS). A manual literature search was also conducted. A total of 12 studies met inclusion criteria, therefore, were analyzed in this review. Results: CUS shares similiar clinical and microscopic features to those found in oral lichen planus (OLP) and oral lichenoid lesions (OLL). Hence, direct immunofluorescence (DIF) is indispensable to define a final diagnosis. Due to the poor sample availability in the current literature, it is not possible to accurately confirm the prevalence and features of CUS. Conclusion: in order to better evaluate this condition’s findings, further studies with a greater amount of similar immune-mediated diseases should be performed.
Keywords: Chronic ulcerative stomatitis; Immune-mediated diseases; Immunofluorescence; Lichen planus